The teeth and claws of the Buddha: monastic warriors and sōhei in Japanese history - Repp, Martin (Japanese religions, 2009)
Review of Adolphson, Mikael S. The teeth and claws of the Buddha: monastic warriors and sōhei in Japanese history. Publisher: Honolulu : Univ of Hawai'i Pr, 2007. ISBN: 978-0-8248-3064-9.